What consumers, general practitioners and mental health professionals want: the co-design and prototype testing of a transdiagnostic, acceptance and commitment therapy-based online intervention to reduce distress and promote wellbeing among Australian adults - Donna Hughes-Barton; Gemma Skaczkowski; Chloe Fletcher; Deborah Turnbull; Janne McMahon; Kate M. Gunn (BMC, 2023)
Abstract Background Many Australians experience mental health challenges, but only a third access face-to-face psychological services, due to multiple barriers including long waitlists. Additional strategies to prevent or help people de-escalate distress at an early stage are needed. Web-based mental health interventions are becoming increasingly acceptable to consumers and referring General Practitioners (GPs), but most are designed for specific disorders/populations. This study explores consumers' and health professionals' preferences and recommendations for the design of a transdiagnostic, Acceptance and Commitment Therapy (ACT)-based, online intervention for Australian adults. Methods Thirty-five people (consumers, carers, GPs, mental health professionals) participated in one or more co-design stages. Stage 1: semi-structured interviews to establish what is wanted from such websites (n = 22). Stage 2: feedback emailed on branding options (n = 20). Stage 3: feedback provided via Zoom or an online survey after testing a website prototype (n = 19). Data were analysed using Thematic Framework Analysis and descriptive statistics. Results Stage 1 highlighted nine key design principles (plus 25 subthemes) that participants emphasised as important to ensure the website would have broad appeal and meet their needs: (1) user choice is valued highly; (2) ACT-based content is acceptable as it is focused on helping people be proactive and 'get unstuck'; (3) non-pathologising, direct, empowering, lay language is endorsed; (4) a positive look and feel is appreciated; (5) images and videos are important to break up text and maintain engagement; (6) short text messages to aid engagement are valued; (7) provision of tailored psychoeducation for highly distressed and suicidal users is endorsed; (8) personal and proactive brand name is preferred (icanactnow); (9) diverse marketing and training activities are recommended. In Stage 2, icanactnow branding preferences were elicited (simplicity, colours to represent growth and a call to action). Stage 3 resulted in the inclusion of a safety plan template and a tailored entry portal for people referred to icanactnow by health professionals. High levels of satisfaction with the prototype were reported. Conclusions These findings informed icanactnow and provide insights for the development of other online mental health interventions, in ways that appeal to both consumers and professionals recommending them.